Immunology Pedagogical Psychology of Pesantren Kindergarten: Multicase Study at Pesantren Kindergarten in Yogyakarta - Suyadi, Suyadi (LPPM IAIN Kudus, 2019)
Normatively, children's education is the responsibility of the family. But when families experience disharmony, even broken home, children's education prone to be abandoned. When a modern school has not been able to maximally accommodate broken home children, Early Childhood Pondok Pesantren/pontren becomes the best alternative choice. The purpose of this research is to find the best alternative education for broken home children in the modern era. This research was conducted throughout 2017 at Early Childhood Pesantren Baiquniyah Yogyakarta. This research was using the qualitative approach, while data collection techniques were observations, interviews, and documentation; data analysis was done in descriptive, interpretative, and comparative. The results show that Baiquniyah Early Childhood Pontren Yogyakarta can be the best alternative choice. This is because the Baiquniyah Early Childhood Pontren Yogyakarta is able to bring the children closer to their parents psychologically, even when they are biologically separated. This condition has implications for the increase of pedagogical immunity, in which children are not easy to stress and depression, thus comfortable in studying at pesantren.